Why the confusion? Reasons and remedies for shortcomings and progress in modernization theory. Issue 7 (2nd October 2020) - Fritzsche, Erik; Vogler, A.
ABSTRACT: Lipset's "well-to-do" quote coined decades of debate on the interaction between economic performance and democracy. However, results remain preliminary and unsatisfying. Many authors report a strong relationship while others deny it. Our paper first reviews research on the impact of (1) both economic growth and general economic performance on overall democracy, (2) the chance of transition towards democracy, and (3) the chance of a democracy to avoid autocratic regression. We demonstrate ambiguity throughout and that no clear picture on potential relations between economic performance and democracy has emerged so far. In a second step, we discuss reasons for this ambiguity. We take insights from methodological research on false-positive findings and draw insights for modernization theory research. Particularly, we identify problems and challenges on both the dependent and the independent variables of modernization theory modelling which cause considerable flexibility of research design and, therefore, making false-positive findings more likely. For each issue, we make suggestions for further research.